UPAYA INDONESIA MENGEKSPOR RENDANG SUMATERA BARAT KE AMERIKA SERIKAT - Sofia Agustia; Umi Oktyari R. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Trading is essential for countries. It can be achieved by export. Indonesia is trying to get access for its products, especially the renewable ones. Food like rendang as one of the most delicious food in the world becomes a comodity for export that can be developed. United States of America is a prospective export destination for rendang. This research describes Indonesia’s efforts to get better access to export rendang to America.               This research was descriptive qualitative. Data was acquired from interviews with authorites working for trade and micro and and small business players. To get detailed and reliable data, researchers also collected documents from books, journals, websites, and government official papers. Liberalism perpective for competitive advantage was used to analyze the data.               The research shows efforts done by Indonesia to improve West Sumatera’s rendang to the United States were registering rendang to UNESCO to get intellectual property rights as an Indonesian traditional food, establishing rendang centers for production, improving the  international standardization, and expanding micro and small businesses internally. Indonesia also has introduced the food at bazaars at Indonesian events sponsored by Indonesian embassy and consulats in the United States for culinary diplomacy. Key Words: Effort, Rendang, Export, Government of Sumatera Barat, culinary diplomacy.